(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2021)
The article deals with the interrelationships of light, space and matter as catalyst and sensitive elements in the construction of the scene’s image. We will approach the theme through the points of view of neuroscience, philosophy and the arts on the relevance of recognizing the subjectivities of these compositional elements to broaden the discussion in the field of perception and interactivity of languages in the theatrical scene and the visuality of the scene and rethink new awareness dynamics with light, matter and space as methodological actions in the formation of the scenic illuminator. In the body of the article, we also bring some reports and practical experiences where we observed some subjective aspects of the creative processes of scenic design artists that complement the article’s theme.